ULTRASONOGRAPHY AND COLOUR DOPPLER CHARACTERISATION OF CERVICAL LYMPHADENOPATHY WITH PATHOLOGICAL CORRELATION - Ashis Kumar Satapathy; Santosh Kumar Padhy; Sibani Patro; Rajesh Pattanaik (Student's Journal of Health Research, 2023)
Aim: The purpose of this study is to evaluate the efficacy of ultrasonography and Doppler in differentiating between benign and malignant cervical lymphadenopathy, and to correlate the results with those of other diagnostic procedures, such as fine needle aspiration cytology (FNAC) / histopathology. Methods: This was a cross-sectional study with diagnostic test evaluation as its methodology. All suspected cases of cervical lymphadenopathy referred to the Department of Radiodiagnosis at IMS and SUM Hospital, Bhubaneswar for sonological evaluation were included in the study. In the study, approximately 70 patients underwent grayscale and colour Doppler sonography of cervical lymphadenopathy. Results: In our research, we observed that out of a total of 128 lymph nodes, 11 exhibited matting, which were all identified as tubercular in nature. For predicting malignant lymph nodes, our study had a high sensitivity of 98.75%, Specificity of 85%, positive predictive value of 81.44%, and negative predictive value of 99.03%. Conclusion: Grey scale ultrasonography can be supplemented by colour Doppler ultrasonography (USG) in patients presenting with cervical lymphadenopathy in order to differentiate between benign and malignant lesions, thereby minimising the number of unnecessary biopsies.